The Swings of Science From Complexity to Simplicity and Back - Pismen, Len (Springer International Publishing, 2018)
This book is a personal account of some aspects of the emergence of modern science, mostly from the viewpoint of those branches of physics which provided the much needed paradigm shift of "more is different" that heralded the advent of complexity science as an antidote to the purely reductionist approach in fundamental physics. It is also about the humans that have helped to shape these developments, including personal reminiscences and the realization that the so-called exact sciences are inevitably also a social endeavour with all its facets. Served by the razor-sharp wit of the author, this erudite ramble is meant to be neither comprehensive nor systematic, but its generous insights will give the inquisitive academically trained mind a better understanding of what science, and physics in particular, could or should be about.